2021
DOI: 10.1186/s12937-021-00747-9
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double-blind, placebo-controlled, multicenter study assessing the efficacy of magnesium oxide monohydrate in the treatment of nocturnal leg cramps

Abstract: Background Magnesium supplements are widely used for prophylaxis and treatment of nocturnal leg cramps (NLC). However, there is little evidence in support of their effectiveness. The main impediment stems from the lack of assessments of cellular absorption. In the current study, we tested the efficacy and safety of a magnesium supplement – magnesium oxide monohydrate (MOMH), for which increased cellular absorption rates were demonstrated in an ex-vivo setting. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Two randomized control studies out of Ukraine and Thailand have shown that increasing magnesium uptake can help relieve pregnancy-induced leg and muscle cramps 6 . It is an effective, safe treatment for nocturnal leg cramps 7 . However, smaller studies suggest that magnesium oxide is not significantly better than a placebo for the older population.…”
Section: Discussionmentioning
confidence: 99%
“…Two randomized control studies out of Ukraine and Thailand have shown that increasing magnesium uptake can help relieve pregnancy-induced leg and muscle cramps 6 . It is an effective, safe treatment for nocturnal leg cramps 7 . However, smaller studies suggest that magnesium oxide is not significantly better than a placebo for the older population.…”
Section: Discussionmentioning
confidence: 99%
“…Quinine has been shown to be effective in treating NLCs but is not recommended by the US Food and Drug Administration due to severe side effects (6). Magnesium supplements are often used as a preventative treatment for NLCs (7,8); however, their effectiveness is controversial (2,9,10). Magnesium supplements are widely marketed for the prophylaxis of NLCs since a double-blind, placebo-controlled study proved their effectiveness in pregnant women (11).…”
Section: Introductionmentioning
confidence: 99%